ORGANIZATIONAL CULTURE TRANSFORMATION IN DEVELOPING DIGITAL COMMUNICATION STRATEGIES AT ALFAGIFT COMPANY - Nababan, Fanny Agustina; Girsang, Lasmery RM (TOPLAMA, 2024)
This research aims to contribute to changes in an organizational culture that is influenced by certain factors, such as in this research, namely due to factors developing communication strategies and changes towards digitalization. This research is descriptive qualitative research using direct observation methods and in-depth interviews in Alfagift. This research uses phenomenological research with the Kurt Lewin Model (unfreezing, changing, and refreezing), and based on the results of this research it shows that the unfreezing process is a process of acceptance of the transformation that will be carried out in an organizational culture by all its members, then in the transformation process to its implementation is carried out by all members of the organization by carrying out their duties and obligations and being ambitious about the change process, and the last is the process of refreezing or mixing/merging attitudes and behavior towards the new culture. Therefore, the role of management is very important to provide support for every process of transformation that occurs carried out to increase the chances of success in creating a new organizational culture towards digitalization.